Experimental Study of Some Agro-Industrial Residues Targeted As Partial Substitutes to Fuel-Oil Conventional Burnt Into the Clinker Kiln of Onigbolo-Cement-Complex (Benin) - SANYA, EMILE ADJIBADÉ; CHAFFA, GÉDÉON; HOUNGBEDJI, F. Martin; BASSITOU, Djima M.A. (My University, 2016)
Cement industry belonged to the largest energy consumers’ factories in Benin. The Cement Complex of Onigbolo (CCO) had particularly undergone the disconcert effects of petroleum blaze costs of last years. This paper dealt with experimental investigations on agricultural/industrial wastes as fractional substitutes of the 7,000 L/h fuel-oil burnt in CCO-clinker furnace. Combustion of about 58 tons of five targeted agro-wastes and worn-tires, up to now ignored or forsaken in situ, even incinerated in open-air because unwieldy, made it possible saving more than 1.5 MF(CFA) in only 100-hours running. Experimental results also showed how far the cement process could contribute to towns/villages/cities cleanup (environmental problems reduction) combined with energy needs fulfillment. Among the studied agro-wastes and in expectation of adequate control and optimization of the convenient pretreatment for improving worn-tires’ combustion, results revealed that wood-sawdust was the alternate-fuel technically and economically well adapted to this tested furnace, better than cottonseeds-hulls preferred by CCO-authorities. Compatibility of the burnt wood-sawdust with cement quality characteristics, relatively high calorific value, availability and abundance throughout the year at existent sawmills, technically justified its choice. Conversely, results furthermore proved that no significant substitution rate can be reached, using only one kind agro-waste: therefore cottonseeds-hulls can be combined to sawdust.
Keywords: alternate-fuels; cotton-fibers waste; cottonseed hulls; clinker kiln/furnace; worn-tires; wood-chips; wood sawdust